Enhancing School Efficiency with A Web-Based E-Reporting System: [Peningkatan Efisiensi Sekolah dengan Sistem E-Reporting Berbasis Web] - Rahayu, Priskila Christine; Monika Karnadi; Christopher Nata (FaST - Jurnal Sains dan Teknologi (Journal of Science and Technology), 2025)
The education sector, a crucial component of the service industry, faced significant challenges in improving operational optimization, particularly in administrative processes. Managing grades and preparing report cards often presented a substantial workload for educators, especially in SMA Santa Patricia. This study aimed to develop an integrated web-based e-Report system to optimize operations by addressing ineffectiveness, inefficiencies, and human error. The system was developed using the System Development Life Cycle (SDLC) framework with a prototyping model. Usability testing through the Computer System Usability Questionnaire (CSUQ) demonstrated improvements, including a 12% increase in effectiveness and an 8% enhancement in efficiency. Additionally, paired T-test results revealed notable gains in system usefulness (14%), information quality (13%), interface quality (14%), and overall system performance (13%) compared to the previous Microsoft Excel-based system. These results underscore the critical role of integrated systems in streamlining operations within the service industry. Bahasa Indonesia Abstract: Sektor pendidikan, sebagai bagian penting dari industri jasa, menghadapi tantangan besar dalam mengoptimalkan operasional, khususnya dalam proses administrasi. Pengelolaan nilai dan penyusunan rapor sering kali menjadi beban kerja yang cukup besar bagi para pendidik, terutama di SMA Santa Patricia. Penelitian ini bertujuan untuk mengembangkan sistem e-Rapor berbasis web yang terintegrasi guna mengoptimalkan operasional dengan mengatasi ketidakefisienan, ketidakefektifan, dan kesalahan manusia. Sistem ini dikembangkan menggunakan kerangka kerja System Development Life Cycle (SDLC) dengan model prototyping. Uji kegunaan yang dilakukan melalui Computer System Usability Questionnaire (CSUQ) menunjukkan adanya peningkatan, termasuk peningkatan efektivitas sebesar 12% dan efisiensi sebesar 8%. Selain itu, hasil paired T-test mengungkapkan peningkatan yang signifikan dalam kegunaan sistem (14%), kualitas informasi (13%), kualitas antarmuka (14%), dan kinerja sistem secara keseluruhan (13%) dibandingkan dengan sistem sebelumnya yang berbasis Microsoft Excel. Hasil ini menegaskan peran penting sistem terintegrasi dalam menyederhanakan operasional di sektor jasa.